Characterization and antimicrobial activity of Streptomyces strains from soils in southern Thailand - Paranee Sripreechasak, Khanit Suwanborirux and Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2014)
Streptomyces strains are superior to other actinomycete strains in their ability to produce large numbers and varieties of antibiotics. The aim of this research was to study on the identification and antimicrobial activity of Streptomyces strains which were isolated from thirteen soil samples collected around Angthong Islands National Park, Surat Thani province, the southern part of Thailand. Twenty-six strains were isolated by using the dilution plating method on starch casein nitrate agar plate and potato starch-glycerol agar plate. On the basis of phenotypic characteristics and the 16S rRNA gene sequence analysis, they were belonged to the genus Streptomyces and were identified as S. tendae (5 isolates), S. malachitospinus (2 isolates), S. marokkonensis (2 isolates), S. parvulus (2 isolates), S. fragilis (1 isolate), S. diastaticus (1 isolate), S. drozdowiczii (1 isolate), S. olivochromogenes (1 isolate), S. aureus (2 isolates), S. iranensis (1 isolate), S. rapamycinicus (1 isolate), S. yatensis (1 isolate), S. samsunensis (4 isolates) and S. spiralis (2 isolates). On the antimicrobial activity screening, 15 isolates exhibited activity against Bacillus subtilis ATCC 6633, 13 isolates against Kocuria rhizophila ATCC 9341, 6 isolates against Mucor racemosus IFO 4581 and Candida albicans KF1, one isolate against Escherichia coli NIHJ KB213 and 5 isolates against Xanthomonas campestris pv. oryzae KB88.
Keywords: Actinomycetes, Streptomyces, antimicrobial activity, soil.